Estudio de prefactibilidad para el montaje de una empresa dedicada a la construcción y comercialización de acuarios acuapónicos y peces ornamentales en la ciudad de Bogotá (2015)
In the industry of aquaculture and rural and urban agriculture, an opportunity has been identified with the growth in the international demand for ornamental fish and organic agricultural products, for which a company is required to design, build and commercialize structures that allow the reproduction of fish and plants of consumption of sustainable way. In order to implement a sustainable and commercially attractive methodology, it has been used to develop this degree work that includes pre-feasibility analysis to create a company that structures urban aquaponics systems for the development of vegetable crops for consumption and fish for ornamentation and marketing.